Techniques of establishing an environmental management system in oil ‎Enterprise - Benterbeh Benterbeh (Dirassat Journal Economic Issue, 2020)
protection the environment ,respect the convention  and application of all capabilities to working in a healthy environment and secure clean perimeter , all this data the business organization seeking to achieve it ; through its plans in all production stages , because now it become one of the most important measures of the international competitiveness. The quality become a requirement and specified basic for competitive, as the environmental component and quality are two sides of the same coin.   The petroleum companies are one of the organizations are concerned about quality and competitiveness , so that the EMS is one of the mechanisms to achieve this requirement  due to the nature of the oil companies activities and complex technologies of petroleum industries. So the effects of petroleum companies activities and quality in the oil industries are raises as a essential parameter in application of this type  companies ,and influential on effectiveness and success of EMS